Biodiversity in the Etymology of Haor Wetland Basin in Bangladesh - Chakraborty, Tapas Ranjan (Journal of Natural Language and Linguistics, 2025)
Bangladesh is a land of wetlands. Many phases, idioms and sayings in the wetland areas of the country are originated and or evaluated from the wetland biodiversity. Etymological researches can help communities understand the insight of their existence with nature. A study on the biodiversity in etymology of wetland basin in Bangladesh was conducted between January and September 2024 in the Medir Haor located in Nasirnagar sub-district under Brahmanbaria district. The research objective was to explore the importance of etymology in wetland conservation attempts. Around 50 people including elderly and youth interacted during interviews and consultations. Twenty species precisely and more biodiversity in gross were identified associated with etymology of Haor wetland. The use of certain animal-related phrases, idioms, and sayings is gradually fading from everyday language. Etymology gives evidence of the status of past and present biodiversity of an ecosystem. Knowing the etymology will help people redefine the touch with the ecosystem and that will help the community feel more ownership in conservation actions. A more effective conservation strategy might incorporate etymological insights—indeed, such wisdom could have shaped conservation policies with greater foresight.